2001
DOI: 10.1523/jneurosci.21-18-07143.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal P2X7Receptors Are Targeted to Presynaptic Terminals in the Central and Peripheral Nervous Systems

Abstract: The ionotropic ATP receptor subunits P2X(1-6) receptors play important roles in synaptic transmission, yet the P2X(7) receptor has been reported as absent from neurons in the normal adult brain. Here we use RT-PCR to demonstrate that transcripts for the P2X(7) receptor are present in extracts from the medulla oblongata, spinal cord, and nodose ganglion. Using in situ hybridization mRNA encoding, the P2X(7) receptor was detected in numerous neurons throughout the medulla oblongata and spinal cord. Localizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
209
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(227 citation statements)
references
References 51 publications
12
209
4
Order By: Relevance
“…On the other hand, on the basis of our data, we cannot completely exclude that in addition to some P2X 7 -like antigen there are some "true" P2X 7 receptors present on mossy fiber terminals that act exclusively on targets that are not involved in synaptic transmission; however, we consider this very unlikely, because in a former study (Kukley et al, 2001) we used another antibody directed against P2X 7 and detected no labeling of the mossy fiber projection at all (our unpublished observation). Because all studies that reported presynaptic P2X 7 used the same antibody (raised against residues 576 -595 of rat P2X 7 ; Alomone Labs, Chemicon, Temecula, CA), it will be interesting to see whether future studies can confirm the presence of presynaptic P2X 7 at other nerve terminals (Deuchars et al, 2001;Miras-Portugal et al, 2003;Atkinson et al, 2004;Puthussery and Fletcher, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, on the basis of our data, we cannot completely exclude that in addition to some P2X 7 -like antigen there are some "true" P2X 7 receptors present on mossy fiber terminals that act exclusively on targets that are not involved in synaptic transmission; however, we consider this very unlikely, because in a former study (Kukley et al, 2001) we used another antibody directed against P2X 7 and detected no labeling of the mossy fiber projection at all (our unpublished observation). Because all studies that reported presynaptic P2X 7 used the same antibody (raised against residues 576 -595 of rat P2X 7 ; Alomone Labs, Chemicon, Temecula, CA), it will be interesting to see whether future studies can confirm the presence of presynaptic P2X 7 at other nerve terminals (Deuchars et al, 2001;Miras-Portugal et al, 2003;Atkinson et al, 2004;Puthussery and Fletcher, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported recently, however, that P2X 7 subunits are localized on presynaptic terminals and modulate transmitter release onto hippocampal and spinal cord neurons (Deuchars et al, 2001;Armstrong et al, 2002;Sperlagh et al, 2002). The presence of Ca 2ϩ -permeable P2X 7 receptors on hippocampal mossy fiber terminals (Armstrong et al, 2002;Sperlagh et al, 2002) would be particularly intriguing, because mossy fiber synapses display several forms of short and long-term synaptic plasticity that depend on the accumulation of presynaptic Ca 2ϩ (Castillo et al, 1994;Regehr et al, 1994;Salin et al, 1996;Dietrich et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometry of P2X 7 R involves a trimeric pore that consists of homomultimers [23]. The P2X 7 R is predominantly expressed on cells of hematopoietic origin such as monocytes [24], dendritic cells, T and B lymphocytes, eosinophils, mast cells, but also on various types of glia within the peripheral and central nervous system including microglia, astrocytes, oligodendrocytes, and Schwann cells [25,26]. Moreover, P2X 7 R protein is expressed on epithelial cells, osteoblasts, synoviocytes, and fibroblasts [27][28][29][30].…”
Section: P2x 7 Rmentioning
confidence: 99%
“…This is pertinent because in this region, the source of adenosine and the conditions under which it is released are unresolved. In other autonomic regions, a major source of adenosine may be attributable to the extracellular metabolism of ATP (St. Lambert et al, 1997), and because SPNs are excited by activation of the P2X 7 receptor, whose endogenous ligand is ATP (Deuchars et al, 2001c), it is likely that this is the case in the IML.…”
Section: Preferential Activation Of A1 or A2 A Receptors?mentioning
confidence: 99%